WOMEN IN EDUCATIONAL LEADERSHIP FROM ISLAMIC PERSPECTIVES - Devi Pramitha (EGALITA, 2020)
The capacity of women to become leaders has always been the main question questioned by various groups when the discourse on women's leadership develops in public, especially when debates are related to an Islamic perspective. For women who lead educational institutions, they must be able to lead the institution, be responsible for the achievement of the institution, and are also expected to become leaders and innovators in the institution. Besides that, one must also have leadership skills and human relations and leadership skills that are good to apply the model according to its characteristics, because the real success of an institution lies in the efficiency and effectiveness of the appearance of a leader. This study uses a qualitative approach to literature study methods. From the results of the author's analysis, it can be concluded that: (1) Women have the spirit, skills, and qualities that are not less than men; (2) Requirement for an educational leader is that the educational leader must be able to lead the organization/ institution, is responsible for the achievement of the organization/ institution, is also expected to be leaders and innovators in organizations/ institutions; and (3) both one's biological factor that men and women are not the main requirements in educational leadership